EFEITOS DA AÇÃO ANTRÓPICA NA FAUNA DE LAGARTOS DO PARQUE NACIONAL SERRA DE ITABAIANA, SERGIPE - Xavier, Maria Aldenise; Dias, Eduardo José dos Reis (Revista Nordestina de Zoologia, 2016)
The Parque Nacional Serra de Itabaiana (PNSI) is nature reserve considered appropriate to ecoturism for present a natural beauty, rivers and areas to practice some adventure sports like rappelling and trekking trails. We evaluated whether antropic action negatively affect the distribution of PNSI lizards. Our study, evaluated the relationship between the distance from the main trail of the park with the structural complexity of the environment and the distribution of species of lizards in eight plots of one hectare. We recorded for active search, five species of lizards of the Tropiduridae, Teiidae and Sphaerodactylidae families. The study of the structural complexity of microhabitat pointed out some differences between near and far plots of the main trail. The highest lizard specimes abundance occurred in plots near the track, favored by low humidity. The anthropic action was registered as the fragmentation of areas to open clearings and the main track of the Parque Nacional Serra de Itabaiana influence the community lizards, in the sense that they use the edges to keep their physiological needs and ecological, because this sites there is higher luminosity and lowest air humidity.